Bottlenecks and barriers to effective coverage of early childhood health and development interventions in Guatemala: A scoping review - Kayla Marra; Isabel Espinosa (Pan American Health Organization, 2020)
Objectives. To identify bottlenecks and barriers to effective coverage by Early Childhood Health and Development (ECHD) interventions in Guatemala. Methods. A scoping review of more than 100 peer-reviewed articles, grey literature, and other academic publications was conducted. Articles published from 2005-2019 were considered. Results were analyzed using the Tanahashi model of effective coverage that categorizes coverage by five domains: availability, accessibility, acceptability, contact, and effective coverage. Results. A total of 103 articles were identified, addressing 337 bottlenecks and barriers to effective coverage by ECHD interventions in Guatemala. Most occurred along the acceptability dimension (35.9%). The findings revealed four opportunity spaces: (i) strong political interest and commitment (opportunity for leadership); (ii) vibrant community health networks (opportunity for leverage); (iii) availability of promising evidence-based projects and interventions (opportunity for scale-up); and (iv) strong agency presence (opportunity for collaboration). Conclusions. Most bottlenecks and barriers to ECHD interventions in Guatemala occur around acceptability, followed by accessibility and availability. There is considerable potential for national leadership, leverage, scale-up, and collaboration of ongoing efforts in the country. These results may be used to inform future research and policymaking. The Tanahashi approach is an effective lens of analysis that can be applied to other countries, geographic areas, and contexts in future studies.